Functional Interaction Between BRCA1 and DNA Repair in Yeast May Uncover a Role of RAD50, RAD51, MRE11A, and MSH6 Somatic Variants in Cancer Development - Maresca, Luisa; Lodovichi, Samuele; Lorenzoni, Alessandra; Cervelli, Tiziana; Monaco, Rossella; Spugnesi, Laura; Tancredi, Mariella; Falaschi, Elisabetta; Zavaglia, Katia; Landucci, Elisabetta; Roncella, Manuela; Congregati, Caterina; et al. (Frontiers in Genetics, 2018)
In this study, we determined if BRCA1 partners involved in DNA double strand break (DSB) and mismatch repair (MMR) may contribute to breast and ovarian cancer development. Taking advantage the functional conservation of DNA repair pathways between yeast and human, we expressed several BRCA1 missense variants in DNA repair yeast mutants to identify functional interaction between BRCA1 and DNA repair in BRCA1-induced genome instability. The pathogenic p.C61G, pA1708E, p.M775R and p.I1766S, and the neutral pS1512I BRCA1 variants increased intra-chromosomal recombination in RSY6wt strain. In the mre11, rad50, rad51 and msh6 deletion strains, the BRCA1 variants p.C61G, pA1708E, p.M775R, p.I1766S and pS1215I did not increase intra-chromosomal recombination suggesting that a functional DNA repair pathway is necessary for BRCA1 variants to determine genome instability. The pathogenic p.C61G and p.I1766S and the neutral p.N132K, p.Y179C and p.N550H variants induced a significant increase of reversion in the msh2Δ strain; the neutral p.Y179C and the pathogenic p.I1766S variant induced gene reversion also, in the msh6Δ strain. These results imply a functional interaction between MMR and BRCA1 in modulating genome instability. We also performed a somatic mutational screening of MSH6, RAD50, MRE11A and RAD51 genes in tumor samples from thirty-four patients and identified eight pathogenic or predicted pathogenic rare missense variants: four in MSH6, one in RAD50, one in MRE11A and two in RAD51. Although we found no correlation between BRCA1 status and these somatic DNA repair variants, this study suggests that somatic missense variants in DNA repair genes, may contribute to breast and ovarian tumor development.